Clinical impact of pretransplant use of multiple tyrosine kinase inhibitors on the outcome of allogeneic hematopoietic stem cell transplantation for chronic myelogenous leukemia. Issue 9 (9th June 2017) - Kondo, Takeshi; Nagamura‐Inoue, Tokiko; Tojo, Arinobu; Nagamura, Fumitaka; Uchida, Naoyuki; Nakamae, Hirohisa; Fukuda, Takahiro; Mori, Takehiko; Yano, Shingo; Kurokawa, Mineo; Ueno, Hironori; Kanamori, Heiwa; et al.
Abstract: Tyrosine kinase inhibitors (TKIs) are widely used to treat patients with chronic myelogenous leukemia in the chronic phase (CML‐CP), and outcomes of TKI treatment for patients with CML‐CP have been excellent. Since multiple TKIs are currently available, second‐line or third‐line TKI therapy is considered for patients who are intolerant of or resistant to the previous TKI treatment. Therefore, allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is considered only for patients with disease progression or for patients after treatment failure with multiple TKIs. To reflect the current clinical situation of patients with CML‐CP, we tried to clarify whether prior TKI treatment affects the outcome of allo‐HSCT. Data from 237 patients for whom the number of pretransplant TKIs varied from one to three were used for analysis. Before allo‐HSCT, 153 patients were treated with one TKI, 49 patients were treated with two TKIs and 35 patients were treated with three TKIs. In addition to conventional risk factors, i.e., disease status at transplantation and patient's age, the use of three TKIs before transplantation was identified as a significant adverse factor for prognosis. Nonrelapse mortality rate was higher in patients treated with three TKIs than in patients treated with one or two TKIs. Our results suggest that allo‐HSCT could be considered for young patients with CML‐CP who manifest resistance to second‐line TKI therapy and who have an appropriate donor.